O ethos discursivo do PT e do DEM em spots da campanha eleitoral à Prefeitura de São Paulo em 2008 - Ribeiro, Alice Pasqualina Vitorino (2011)
Based on the problematic Brazilian political relations, I analyze the political discourse during electoral campaign. The analyzed corpus constituted of spots exhibited on the TV during dispute of the São Paulo s town hall, in 2008, by Marta Suplicy (PT) and Gilberto Kassab (DEM) candidates. From procedure lecture based on French Discourse Analysis, as proposed by Maingueneau, and based in the relation between different discourse plans, with focuses on the ethos and cenography notions, the work aims to perceive the sense effects built in political discourses. The corpus constitution and analysis, use evidential paradigm (GINZBURG, 1991), whose proposal is like discourse analyst activity, which characterize fundamentally evidential description which become possible understand different discourse plans. Analyses realized perceive different cenographies. The ethos of candidates might be composed of several traces. DEM enterprise ethos meets traces as competence, informally and humor. PT ethos is more maternal , conservative and aggressive. The research possibility concluding which spots of electoral campaign tend an infantilization process of political discourse, campaign trivialization, with traces of humor, tendency that seeming confirm in the Republic presidential electoral campaign in 2010